APLIKASI TEKNOLOGI CARBOXYMETHIL CELLULOSE (CMC) PADA SIRUP MANGROVE DI DESA MARGASARI, KECAMATAN LABUHAN MARINGGAI, KABUPATEN LAMPUNG TIMUR, PROVINSI LAMPUNG - Hari Kusuma, Anma; Yanvika, Helvi; Yuliandari, Puspita (Jurnal Pengabdian Perikanan Indonesia, 2022)
Mangroves are coastal ecosystems that are able to provide services in the economic and ecological fields. One of them is the utilization of mangrove fruit into syrup processed products. Margasari Village is located in Labuhan Maringgai District, East Lampung Regency, Lampung Province which has very large mangrove potential. So far, there are still shortcomings in the mangrove syrup produced, such as precipitation, so it is necessary to apply Carboxymethyl Cellulose (CMC) technology to improve the quality of the mangrove syrup. This community service combines experience, knowledge and technology for environmental and sustainable mangrove management so as to be able to contribute to alternative livelihood solutions and improve the economy of coastal communities. The method of implementing this activity includes three stages, namely preparation, implementation and evaluation. After this activity is carried out, the people of Margasari Village have increased understanding, knowledge and motivation in utilizing mangrove fruit into syrup products and this product is expected to be one of the village's superior products and understand and increase the awareness of the people of Margasari Village, the importance of mangrove conservation and its sustainable use